2019
DOI: 10.3389/fphys.2019.00685
|View full text |Cite
|
Sign up to set email alerts
|

Pectin Digestion in Herbivorous Beetles: Impact of Pseudoenzymes Exceeds That of Their Active Counterparts

Abstract: Many protein families harbor pseudoenzymes that have lost the catalytic function of their enzymatically active counterparts. Assigning alternative function and importance to these proteins is challenging. Because the evolution toward pseudoenzymes is driven by gene duplication, they often accumulate in multigene families. Plant cell wall-degrading enzymes (PCWDEs) are prominent examples of expanded gene families. The pectolytic glycoside hydrolase family 28 (GH28) allows herbivorous insects to break down the P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…We chose PCO_GH28-1 and -3 as representatives of an active endo-PG and a catalytically inactive pseudoenzyme, respectively. In addition to previous studies in which PCO_GH28-3 did not hydrolyze any of the substrates tested (Kirsch et al, 2012(Kirsch et al, , 2014(Kirsch et al, , 2019, we showed that unlike PCO_GH28-1, the pseudoenzyme no longer binds to pectic substrates (Supplementary Figure 4).…”
Section: Interaction Of B Rapa Ssp Pekinensis Cwps With Pco_gh28-1 and -3supporting
confidence: 75%
See 1 more Smart Citation
“…We chose PCO_GH28-1 and -3 as representatives of an active endo-PG and a catalytically inactive pseudoenzyme, respectively. In addition to previous studies in which PCO_GH28-3 did not hydrolyze any of the substrates tested (Kirsch et al, 2012(Kirsch et al, , 2014(Kirsch et al, , 2019, we showed that unlike PCO_GH28-1, the pseudoenzyme no longer binds to pectic substrates (Supplementary Figure 4).…”
Section: Interaction Of B Rapa Ssp Pekinensis Cwps With Pco_gh28-1 and -3supporting
confidence: 75%
“…Interestingly, some PG family members, including PCO_GH28-3, were inactive on all tested substrates and possessed amino acid substitutions in residues involved in catalysis or substrate binding (Kirsch et al, 2012(Kirsch et al, , 2014. Nonetheless, recent findings suggest that these pseudoenzymes play a role in the pectin digestion pathway, because when they were silenced, food-to-energy conversion in P. cochleariae larvae was less efficient compared to when pseudoenzymes were not silenced (Kirsch et al, 2019). Even though such pseudoenzymes have also been described in other beetles (Kirsch et al, 2014(Kirsch et al, , 2016Pauchet et al, 2014), their function remains elusive.…”
Section: Introductionmentioning
confidence: 98%
“…It took 10 years until they finally found a way to express enough protein to solve the X-ray structure of PvPGIP2 from the bean Phaseolus vulgaris in a complex with the fungal FpPG from Fusarium phyllophilum (52). The difficulty of expressing other PGIPs has resulted in PvPGIP2 being a very well-studied protein (53)(54)(55)(56) that is often used in PGIP assays (33,36,(57)(58)(59). However, which properties enable the expression and increased stability compared with other PGIPs in vitro is unknown.…”
mentioning
confidence: 99%
“…Indeed, coleopterans from families Curculionidae and Chrysomelidae have variable number of Glycosyl hydrolases in their genomes, including endoglucanases 19,23,37 from families GH5, GH9, GH45 and GH48. However, functional validation in vivo is still necessary due to the special feature of non-functional enzymes may act as a decoy to compete with plant-derived enzyme inhibitors, as suggested by Kirsch and colleagues 20 , or even new function acquisition being specific to a different substrate 38 .
Figure 2Relative quantification of AgraGH45-1 in different A. grandis tissues. Quantification in larva ( A ) and adult ( B ) carcass and whole gut.
…”
Section: Resultsmentioning
confidence: 99%
“…Although microorganisms, such as bacteria and fungi, are the primary source of cellulolytic enzymes 1517 , recently it has been found that invertebrates like insects and nematodes possess a whole arsenal of enzymes that degrade plant cell walls, such as glycosyl hydrolases (endoglucanases, polygalacturonases and xylanases) and other pectin-modifying enzymes 18–20 . Remarkably, it has been proposed that insects and nematodes have acquired these enzymes from bacteria and fungi through horizontal gene transfer with many independent events occurring along time 21 .…”
Section: Introductionmentioning
confidence: 99%